Crystal structure of natural product argyrin-D determined by 3D electron diffraction. Issue 33 (9th August 2022) - Gorelik, Tatiana E.; Tehrani, Kamaleddin H. M. E.; Gruene, Tim; Monecke, Thomas; Niessing, Dierk; Kaiser, Ute; Blankenfeldt, Wulf; Müller, Rolf
Abstract : Crystal structure of natural product argyrin D was determined from electron diffraction data. Abstract : The crystal structure of the natural product argyrin D was determined from 3D electron diffraction data. The molecular conformation of the newly determined structure is similar to that of other argyrins. We attribute the exceptional stability of this geometry to an extended intramolecular hydrogen-bonding network.